A comparison of the nutritional profile and nutrient density of commercially available plant-based and dairy yogurts in the United States - D’Andrea, Astrid E.; Kinchla, Amanda J.; Nolden, Alissa A. (Frontiers in Nutrition, 2023)
Introduction: Plant-based yogurts are sustainable alternatives to dairy yogurts, but a nutritional comparison of plant-based yogurts within the context of dairy yogurts has not yet been applied to commercially available products in the United States. Dairy yogurts provide significant dietary nutrients, and substituting plant-based yogurts may have unintended nutritional consequences. The objective of this study was to compare the macronutrient and micronutrient values of commercially available plant-based and dairy yogurts launched between 2016 and 2021. Methods: Nutritional information for yogurts were collected through Mintel Global New Products Database, and products were categorized according to their primary ingredient. Regular-style yogurts (n = 612) were included in this study: full-fat dairy (n = 159), low and nonfat dairy (n = 303), coconut (n = 61), almond (n = 44), cashew (n = 30), and oat (n = 15). We utilized the Nutrient Rich Foods (NRF) Index, a comprehensive food guidance system that assigns a score based on the nutrient density of individual foods. This allowed us to compare the nutritional density of the yogurts based on nutrients to encourage (protein, fiber, calcium, iron, potassium, vitamin D) and nutrients to limit (saturated fat, total sugar, sodium). Results: Compared to dairy yogurts, plant-based yogurts contained significantly less total sugar, less sodium, and more fiber. However, plant-based yogurts contained significantly less protein, calcium, and potassium than dairy yogurts. The yogurts were ranked from the highest to lowest nutrient density based on the NRF Index as follows: almond, oat, low and nonfat dairy, full-fat dairy, cashew, and coconut. Almond yogurts scored significantly higher than all other yogurts, indicating the highest nutrient density. Discussion: The highest NRF scores were awarded to almond and oat yogurts, likely a result of their low levels of total sugar, sodium, and saturated fat. By applying the NRF model to plant-based and dairy yogurts, we have identified opportunities for the food industry to improve the formulation and nutritional composition of plant-based yogurts. In particular, fortification is an opportunity to improve plant-based yogurt nutritional properties.